1975
DOI: 10.1136/bmj.1.5948.17
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-glutamyl transpeptidase, triglycerides, and enzyme induction.

Abstract: SummaryA study conducted on 109 consecutive patients submitted for routine lipid and lipoprotein screening has shown a significant positive association between serumi y-glutamyl transpeptidase ( ,-GT) activity and the serum triglyceride concentration and between serum y-GT activity and the serum pre-P-lipoprotein concentration. We suggest that these associations may reflect hepatic microsomal enzyme induction in hyperlipidaemic subjects which increases the hepatic content of the rate-limiting enzyme(s) for tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1975
1975
1993
1993

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…Elevated serum GGTP levels have been prominently mentioned in the literature as an index of microsoinal enzyme induction in the human (36)(37)(38)(39)(40). Recent studies (41), however, have in part disputed this conclusion.…”
Section: Pcb Effects On Microsomal Enzymesmentioning
confidence: 79%
“…Elevated serum GGTP levels have been prominently mentioned in the literature as an index of microsoinal enzyme induction in the human (36)(37)(38)(39)(40). Recent studies (41), however, have in part disputed this conclusion.…”
Section: Pcb Effects On Microsomal Enzymesmentioning
confidence: 79%
“…In the case of GGT it may well be similar to the increase caused by hepatic microsomal enzyme-inducing drugs, which raise the plasma GGT (Rosalki et al, 1971;Whitfield et al, 1973). Association between increased GGT and raised triglycerides has been reported (Martin et al, 1975), and it was suggested that the increase in triglycerides was also related to enzyme induction.…”
Section: Imentioning
confidence: 96%
“…Elevated cholesterol and triglycerides were found following ethanol (Lefevre, de Carli & Lieber, 1972), phenobarbitone (Jones & Armstrong, 1965) and in patients having increased y-glutamyltranspeptidase (Martin, Martin & Goldberg, 1975). These findings were thought to be due to enzyme induction, and therefore plasma lipids and lipoproteins were investigated in the present study following three different enzyme inducing drugs.…”
mentioning
confidence: 81%